Social movements in Cayaltí: 1915-1919 - Kapsoli, Wilfredo (1978)
The Cayalti hacienda has its origin, like the rest of the haciendas, in the colonial regime. In the middle of the last century we find it dedicated to the production of cotton under the impulses of an external (American secession war) and internal (guano from the islands) situation. Since the end of the century, its main activity has been the production of sugar. The owners of the hacienda, the Aspíllaga family, are of Chilean descent; they had a great spirit of enterprise and active political participation at both the regional and national levels.